SAT0551 Sensitivity of Chest Radiography in the Early Diagnosis of Sarcoidosis: is it Really Should be Done?. (9th June 2015) - Kobak, S.; Saydam, G.; Ince, O.; Sever, F.
Abstract : Background: Sarcoidosis is a chronic granulomatous disease characterized by non-caseating granuloma. The conventional chest radiography has important role in the diagnosis, staging and follow-up of disease. Computed tomography is a second-line imaging method used to determine the extent, complications and diffrential diagnosis of sarcoidosis. Objectives: To determine the sensitivity of coventional chest radiography in the early diagnosis of sarcoidosis and to compare with computed tomography (CT) imaging. Methods: One hundred and nine sarcoidosis patients followed at a single center were included in the study. Demographic, clinical, laboratory and radiological data of all patients were recorded. Conventional chest radiography and computed tomography imaging taken at diagnosis were evaluated retrospectively independently from two radiologists and one rheumatologist. Results: Among 109 patients eighty-one patients' chest radiographies and CT imaging taken at the same center has been reached. Among 81sarcoidosis patients 23 (%28.4) were male, 58 (%71.6) were female. The mean patients age was 46.4year and the mean disease duration was 3.8year. Conventional chest radiography is regarded as normal at diagnosis in 30 patients (37%), while all of these patients had findings consistent with sarcoidosis on CT imaging. CT imaging are more sensitive than conventional chest radiography in the early diagnosis of sarcoidosis (p=0.001). Also CT imaging is more superior for detection of disease extent and complications. Conclusions: In this study, the sensitivity of conventional chest radiography who is accepted as the first-line imaging modality in the diagnosis of sarcoidosis were significantly lower when compared with CT imaging. The use of CT imaging is important for early diagnosis of sarcoidosis. The low sensitivity and specificity of conventional chest radiography is a condition that requires the discussion of this method. Multicenter prospective study are needed in this regard. References: Traill ZC, Maskell GF, Gleeson FV. High-resolution CT findings ofpulmonary sarcoidosis. JRA m J Roentgenol 1997;168:1557–1560. Akira M, Kozuka T, Inoue Y, et al. Long-term follow-up CT scanevaluation in patient with pulmonary sarcoidosis. Chest 2005; 127:185-191. Baughman RP, Teirstein AS, Judson MA et al. Clinical characteristicsof patients in a case control study of sarcoidosis. Am J Respir CritCare Med 2001;164:1885-1889). Kirks DR, McCormick VD, Greenspan RH. Pulmonary sarcoidosis.Roentgenologic analysis of 150 patients. Am J Roentgenol RadiumTher Nucl Med 1973;117:777–786. Disclosure of Interest: None declared